Multidosing Intramuscular Administration of Methotrexate in Interstitial Pregnancy With Very High Levels of β-hCG: A Case Report and Review of the Literature - Conti, Valeria; Luciano, Giovanni; Pecoraro, Giovanni; Iovieno, Roberto; Filippelli, Amelia; Guida, Maurizio (Frontiers in Endocrinology, 2018)
Ectopic pregnancy (EP) is the implantation of an embryo outside the endometrial cavity of the uterus. Signs and symptoms of EP may arise between the 6th and the 8th week of gestation and include vaginal bleeding, lower abdominal and pelvic pain. Frequently EPs implant in the fallopian tubes. A rare EP is the interstitial pregnancy, a life-threatening condition being responsible for nearly 20% of all deaths caused by EPs. Because of its unique location, the diagnosis is difficult and based on signs and specific criteria together with measuring of serum β-hCG. Usually, EP is treated by surgical approach, which is associated with increased morbidity, decreased fertility and increased likelihood of hysterectomy and uterine rupture in a subsequent pregnancy. Early diagnosis is crucial to life saving and allowing alternative therapeutic interventions such as pharmacological treatments. Methotrexate (MTX) represents the mainstay therapy. There is no standard care for the interstitial pregnancy for what concerns either surgical or pharmacological approaches. We reported a case of a 36-year-old woman admitted to the Hospital of Salerno-Italy with a value of serum β-hCG of 35993 IU/L. Transvaginal ultrasonography revealed an empty uterine cavity and a mass of 35.7 mm in diameter characterized by a hypoechoic central area. The patient was in stable haemodynamic condition and no haematologic, renal and hepatic impairments were recorded. Despite the high serum β-hCG levels, a pharmacological approach was preferred to a surgical one. The patient was treated with intramuscular administration of MTX in daily dose of 1 mg/Kg alternated with 0.1 mg/kg folinic acid for 5 days. The patient remained hospitalized for 20 days and no side effects were reported. The decrease of the serum β-hCG was monitored and more than 15% reduction was detected between the 4th and the 7th day after the beginning of the treatment. The serum β-hCG became undetectable 35 days after. A multidosing intramuscular administration of MTX was effective and safe even in the presence of very high serum β-hCG levels. Together with similar cases reported in literature, the present results can contribute to improve the decision making in the treatment of the interstitial pregnancy.